Variations in genetic diversity in cultivated Pistacia chinensis - Han, Biao; Zhang, Ming-Jia; Xian, Yang; Xu, Hui; Cui, Cheng-Cheng; Liu, Dan; Wang, Lei; Li, De-Zhu; Li, Wen-Qing; Xie, Xiao-Man (Frontiers in Plant Science, 2022)
Identification of the evolution history and genetic diversity of a species is important in the utilization of novel genetic variation in this species, as well as for its conservation. Pistacia chinensis is an important biodiesel tree crop in China, due to the high oil content of its fruit. The aim of this study was to uncover the genetic structure of P. chinensis and to investigate the influence of intraspecific gene flow on the process of domestication and the diversification of varieties. We investigated the genetic structure of P. chinensis, as well as evolution and introgression in the subpopulations, through analysis of the plastid and nuclear genomes of 39 P. chinensis individuals from across China. High levels of variation were detected in the P. chinensis plastome, and 460 intraspecific polymorphic sites, 104 indels and three small inversions were identified. Phylogenetic analysis and population structure using the plastome dataset supported five clades of P. chinensis. Population structure analysis based on the nuclear SNPs showed two groups, clearly clustered together, and more than a third of the total individuals were classified as hybrids. Discordance between the plastid and nuclear genomes suggested that hybridization events may have occurred between highly divergent samples in the P. chinensis subclades. Most of the species in the P. chinensis subclade diverged between the late Miocene and the mid-Pliocene. The processes of domestication and cultivation have decreased the genetic diversity of P. chinensis. The extensive variability and structuring of the P. chinensis plastid together with the nuclear genomic variation detected in this study suggests that much unexploited genetic diversity is available for improvement in this recently domesticated species.